Sensitive Quantitative Analysis of the Meconium Bacterial Microbiota in Healthy Term Infants Born Vaginally or by Cesarean Section - Nagpal, Ravinder; Tsuji, Hirokazu; Takahashi, Takuya; Kawashima, Kazunari; Nagata, Satoru; Nomoto, Koji; Yamashiro, Yuichiro (Frontiers in Microbiology, 2016)
For decades, babies were thought to be born germ-free, but recent evidences suggest that they are already exposed to various bacteria in-utero. However, the data on population levels of such pioneer gut bacteria, particularly in context to birth mode, is sparse. We herein aimed to quantify such bacteria from the meconium of 151 healthy term Japanese infants born vaginally or by C-section. Neonatal first meconium was obtained within 24-48 hours of delivery; RNA was extracted and subjected to reverse-transcription-quantitative PCR using specific primers for Clostridium coccoides group, Clostridium leptum subgroup, Bacteroides fragilis group, Atopobium cluster, Prevotella, Bifidobacterium, Lactobacillus, Enterococcus, Enterobacteriaceae, Staphylococcus, Enterococcus, Streptococcus, Clostridium perfringens, and C. difficile. We detected several bacterial groups in both vaginally- and cesarean-born infants. B. fragilis group, Enterobacteriaceae, Enterococcus, Streptococcus and Staphylococcus were detected in more than 50% of infants, with counts ranging from 105-108 cells/g sample. About 30-35% samples harbored Bifidobacterium and Lactobacillus (104-105 cells/g); whereas C. coccoides group, C. leptum subgroup and C. perfringens were detected in 10-20% infants (103-105 cells/g). Compared to vaginally-born babies, cesarean-born babies were significantly less often colonized with Lactobacillus genus (6% vs. 37%; P=0.01) and L. gasseri subgroup (6% vs. 31%; P=0.04). Overall, seven Lactobacillus subgroups/ species i.e. L. gasseri subgroup, L. ruminis subgroup, L. casei subgroup, L. reuteri subgroup, L. sakei subgroup, L. plantarum subgroup and L. brevis were detected in the samples from vaginally-born group, whereas only two members i.e. L. gasseri subgroup and L. brevis were detected in the cesarean group. These data corroborate that several bacterial clades may already be present before birth in term infants’ gut. Further, Remarkably lower detection rate prevalence of lactobacilli in cesarean-born babies suggests that the primary source of lactobacilli in infant gut is mainly from maternal vaginal and─to a lesser extent─anal microbiota during vaginal delivery, and that the colonization of some important Lactobacillus species is delayed in babies delivered via cesarean-section.